Investigation of elastic scattering of alpha-particles from 12C in optical and folding models - Буртебаев, Н.; Джансейтов, Д.; Керимкулов, Ж.; Жолдыбаев, Т.; Алимов , Д.; Мухамеджанов, Е.; Насурлла, М.; Ходжаев, Р.; Аймаганбетов, А.; Амангелдi, Н.; Ерғалиұлы, Г.; Фомичёв , А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Processes of elastic scattering of alpha-particles from 12C nuclei at energy 50 MeV was studied in this paper. The experimental angular distributions of the elastic scattering of alpha particles on 12C nuclei were measured on the extracted beams of the isochronous cyclotron U-150M of the Institute of Nuclear Physics (Almaty, Kazakhstan). Registration and identification of the scattered reaction products was carried out by the ∆E − E telescope of silicon semiconductor detectors. The differential cross sections measured at laboratory system in the range 10o − 170o. Analysis of elastic scattering was made within optical model. Both microscopic double folding potentials and phenomenological potentials were used for real part of complex nuclear potential. Imaginary part had the shape of phenomenological surface Woods-Saxon potential. The calculated theoretical cross sections are in good agreement with experimental data. The results obtained in this paper will be used to analyze the inelastic scattering of alpha particles by 12C nuclei and in the 3He reaction on a 13C target.